The Influence of Corporate Integrity Culture on Disclosure of ‎Key Audit Matters - Fang, Chen Ji; Ahmi, Aidi; Sharif, Zakiyah (International Journal of Accounting and Economics Studies, 2025)
Integrity is the foundation of how companies operate, and a culture of integrity is vital for reducing corporate risks and building trust in ‎capital markets. Using data from China’s A-share-listed companies from 2019 to 2024, this study explores how corporate integrity culture ‎influences the disclosure of Key Audit Matters (KAMs) and the mechanisms behind this relationship. The results show that a strong integri-‎ty culture is linked to fewer KAM disclosures. This connection works through several pathways: lowering business risks, reducing finan-‎cial risks, and decreasing auditors’ legal exposure. Analysis of different groups suggests that the negative impact of integrity culture on ‎KAM disclosure is stronger in firms with many relational transactions and high institutional investor participation. Additional findings indi-‎cate that companies with a strong integrity culture tend to pay lower audit fees, produce fewer KAMs with inconclusive assessments, and ‎have less similarity in KAM disclosures within the same industry, often with a less positive tone. Ultimately, this research recommends that ‎companies develop long-term integrity-focused management systems to strengthen their cultural influence and support high-quality growth. ‎Auditors should consider corporate cultural traits to improve audit efficiency and quality. Policymakers are advised to encourage firms to ‎build their integrity culture, fostering healthy development within capital markets‎.